Effects of edible oil and fat-soluble vitamins on acrylamide formation in a chemical model system and during intermittent deep-fat frying of french fries - Kuek, Su Lee (2020)
High concentration of acrylamide had been identified in fried potato products. However, the effect of edible oils and fat-soluble vitamins toward acrylamide had yet to be determined clearly. The objectives of this study were firstly to determine the contributions of edible oils in terms of type of vegetable oils and number of frying cycles toward acrylamide formation. Second objective is to determine the relationship of fatty acid composition (FAC) and total polar compound fraction (TPC) of vegetable oils on acrylamide during intermittent deep-fat frying of French fries. The third objective was to determine effect of different levels of vitamin A and E homologs on acrylamide formation in Asparagine-Glucose model system. Par-fried potato strips were fried in four types of vegetable oils i.e., palm olein, red palm olein, sunflower oil and soybean oil for 80 cycles. Acrylamide concentration in French fries were analysed. Oils used every 16ᵗʰ cycle of frying were analysed for peroxide value (PV), p-anisidine value (p-AV), total oxidation value (TOTOX) and free fatty acid (FFA). Consequently, frying cycle significantly affected acrylamide concentration in all oils except palm olein. A weak positive, however significant correlation were found between acrylamide with p-AV and FFA; but not PV and TOTOX. Furthermore, FFA contribute more to acrylamide formation compare to p-AV. For the second study, FAC and TPC of vegetable oils at every 16ᵗʰ frying cycle were analysed. Saturated fatty acid (SFA) increased and polyunsaturated fatty acid (PUFA) decreased as number of frying cycle increased for all oils. Significant positive correlation was observed between SFA, monounsaturated fatty acid (MUFA), PUFA and acrylamide concentration with PUFA being the strongest. TPC and polar compound fractions in terms of polymerised triacylglycerol (PTAG), oxidised triacylglycerol and diacylglycerol of all vegetable oils increased significantly across 80 frying cycles. Weak but significant negative correlation was observed between PTAG of vegetable oils and acrylamide. For the third study, six vitamin homologs, i.e., beta- carotene (BC), alpha-tocopherol (AT), delta-tocopherol (DT), alpha-tocotrienol (ATT), delta-tocotrienol (DTT) and gamma-tocotrienol (GTT), were individually added at the level of 1 and 10 µmol into the model system and heated at 160°C for 20 minutes. AT, DT and GTT at 1 µmol significantly increased acrylamide concentration when compared to control with AT being the highest. All homologs at 10 µmol except DT significantly increased acrylamide with BC being the highest. BC significantly increased acrylamide when its level increased. AT, DT and GTT significantly decreased acrylamide when their levels increased. Vitamin A and E homologs enhanced acrylamide formation. However, its levels can determine their effects as antioxidant or pro-oxidant. Thus, edible oils during frying as well as fat-soluble vitamins play a significant role in acrylamide formation.